Experimental Study : Thermal Variations and Pressure's Impact on Plastic Injection Molding Quality - Leksonowati, Nur Fitria; Pamungkas, Nurman; Manurung, Meilani Mandalena (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
This study investigates the effects of varying hot water temperatures (75℃, 85℃, and 95℃) and injection pressures (328 Bar and 928 Bar) on the outcomes of experimental tests in injection molding. Results indicate that at 75℃, 85℃, and 95℃ with an injection pressure of 328 Bar, the product displayed a Short Mold defect despite a slight increase in mass. At 75℃ with an increased injection pressure of 928 Bar, a White Line defect was observed, while at 85℃ and 928 Bar, a defect-free part was produced with optimal mass. However, at 95℃, a Bright Color defect was evident, leading to part rejection despite a slight mass increase. The findings highlight the significance of meticulous parameter selection, with an optimal combination identified as 85℃ hot water temperature and 928 Bar injection pressure for defect-free production in injection molding processes.